Participant Authenticating, Error Detecting, and 100% Multiple Errors Repairing Chang-Chen-Wang's Secret Sharing Method Enhancement - Chefranov, Alexander G.; Narimani, Amir (Assoc Computing Machinery, 2016)
Chang-Chen-Wang's (3,n) Secret grayscale image Sharing between n grayscale cover images method with participant Authentication and damaged pixels Repairing (SSAR) properties is analyzed; it restores the secret image from any three of the cover images used. We show that SSAR may fail, is not able fake participant recognizing, and has limited by 62.5% repairing ability. We propose SSAR (4,n) enhancement, SSAR-E, allowing 100% exact restoration of a corrupted pixel using any four of n covers, and recognizing a fake participant with the help of cryptographic hash functions with 5-bit values that allows better (vs. 4 bits) error detection. Using a special permutation with only one loop including all the secret image pixels, SSAR-E is able restoring all the secret image damaged pixels having just one correct pixel left. SSAR-E allows restoring the secret image to authorized parties only contrary to SSAR. The performance and size of cover images for SSAR-E are the same as for SSAR.
9th International Conference on Security of Information and Networks (SIN) -- JUL 20-22, 2016 -- Rutgers Univ, NJ
Keywords: Steganography; secret image; cover image; secret sharing; error detection; repairing; authentication